2003
DOI: 10.1093/jac/dkg401
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of resistant Streptococcus pneumoniae in an in vitro dynamic model that simulates moxifloxacin concentrations inside and outside the mutant selection window: related changes in susceptibility, resistance frequency and bacterial killing

Abstract: These data suggest that AUC24/MICs >100 h may protect against the selection of resistant S. pneumoniae mutants. Since the usual 400 mg dose of moxifloxacin provides much higher AUC24/MIC (270 h), it is expected to prevent mutant selection at clinically achievable concentrations. Also, these data provide further support for the MSW hypothesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
69
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(82 citation statements)
references
References 18 publications
12
69
0
1
Order By: Relevance
“…Most of these resistant bacteria were still susceptible to the MPC of marbofloxacin for Escherichia coli ATCC 25922 (0.256 g/ml), suggesting that these resistant populations corresponded to those of the first-step mutants. The detection of first-step mutants when marbofloxacin concentrations were maintained within the MSW is in agreement with previous studies (5,10). However, resistant mutants emerged systematically in all three experiments carried out with 10 9 CFU/ml, but only in one of three for the 10 5 -CFU/ml inoculum and one of three for the 10 7 -CFU/ml inoculum.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…Most of these resistant bacteria were still susceptible to the MPC of marbofloxacin for Escherichia coli ATCC 25922 (0.256 g/ml), suggesting that these resistant populations corresponded to those of the first-step mutants. The detection of first-step mutants when marbofloxacin concentrations were maintained within the MSW is in agreement with previous studies (5,10). However, resistant mutants emerged systematically in all three experiments carried out with 10 9 CFU/ml, but only in one of three for the 10 5 -CFU/ml inoculum and one of three for the 10 7 -CFU/ml inoculum.…”
supporting
confidence: 91%
“…The MIC and MPC define the bounds of the mutant selection window (MSW), a range of antibiotic concentrations favoring the selection of the first-step mutant subpopulation (9). Previous studies (5,10) have indicated that the growth of this first-step mutant subpopulation was prevented when fluoroquinolone concentrations exceeded the MPC for more than 80% of the dosage interval, i.e., when time within the MSW (T MSW ) was less than 20%. However, those studies tested only a single inoculum size, but the bacterial load increases during the time course of infections, and the likelihood of a mutant appearing may increase with inoculum size.…”
mentioning
confidence: 99%
“…Testing involving S. aureus and using in vitro dynamic models reveals that drug-resistant mutants fail to amplify when fluctuating fluoroquinolone concentrations are maintained above or below the selection window that has been determined using agar plates; as expected, mutants are selectively amplified when concentrations are between the MIC and the MPC [31]. Similar observations were obtained with S. pneumoniae [32] and by additional experments with S. aureus [26,33,34]. The principle has also been extended to S. aureus for vancomycin and daptomycin [35].…”
Section: Dynamic Models and The Window Hypothesissupporting
confidence: 62%
“…This MSW hypothesis has been used to explain the results of several in vitro studies using an expanded-spectrum cephalosporin (22) and quinolones (7,10,35) against both gram-positive and gram-negative bacterial strains. For quinolones, this was achieved with dosing regimens producing ratios of the AUC at 24 h to MIC of Ͼ100 (10,33,36). In the present study, no distinction could be made between the effects of fTϾMIC and tMSW because of the relative high MPC values of the E. cloacae strain.…”
Section: Discussionmentioning
confidence: 71%
“…While the ratio of the area under the concentrationtime curve (AUC) at 24 h to MIC of Ն100 (10,33,36) or a peak-to-MIC ratio of 8 to 10 (3, 8) may significantly reduce the emergence of resistant subpopulations during treatment with fluoroquinolones and aminoglycosides, it has been reported that these indices do not appear to play an important role in the suppression of resistance during ␤-lactam therapy (33). However, recent findings have indicated the importance of a high-dose, short-elimination half-life regimen to minimize the emergence of cephalosporin-resistant Escherichia coli strains (25).…”
Section: To 10mentioning
confidence: 99%